PENGARUH DURASI DAN WAKTU BELAJAR DI RUMAH TERHADAP HASIL BELAJAR IPA SISWA SMP DAN MTS DI PULAU RIMAU, KABUPATEN BANYUASIN TAHUN AJARAN 2024/2025 - Hamdi Akhsan; Eka Sutinah; Kistiono Kistiono (Physics and Science Education Journal (PSEJ), 2025)
Studying at home plays an important role in improving student achievement, especially in science subjects that are both conceptual and challenging. This study aimed to examine the effect of the duration and time of study at home on students' science learning outcomes. The approach used was quantitative, with a survey and documentation design. The population included all junior and senior high school students in Pulau Rimau in the 2024/2025 school years. A sample of 170 students was selected using Proportional Stratified Sampling. An analysis was conducted to determine the effects of each variable on learning outcomes. The analysis showed that the study duration had a significant effect on learning outcomes (p<0.05). Tukey's HSD further test showed that students who studied less than one hour per day had significantly lower learning outcomes than students who studied 1-2 hours or more than 2 hours. In contrast, the study time showed no significant effect (p>0.05). This finding suggests that the allocation of at least one hour of study time per day contributes positively to science-learning outcomes. Collaboration between parents and teachers so that the duration of study at home is optimal for science achievement.